Nano urea and its Superiority Over urea as Fertilizer Elaborating some Applications - An Overview - Nabanita De,; Tanmoy Das, (International Journal of Scientific Research in Science and Technology, 2024)
Conventional urea, a major source of nitrogen for plants, suffers from losses due to ammonia volatilization and leaching. Nano-urea, with its reduced particle sizes (typically 1-100 nm), offers potential benefits like enhanced nutrient use efficiency and controlled release. This review explores the synthetic methods, characterization techniques, applications in fruit crops and food grains, grain viz. Kharif Paddy wheat Millette, etc. and the advantages and disadvantages of Nano-urea for sustainable and precision agriculture.
Keywords: Nano Urea; Nano-Fertilizer; Precision-Agriculture; Control Release Fertilizer; Slow Release Fertilizer